Engaging Citizens for Better Development Results : An Independent Evaluation - Independent Evaluation Group (World Bank, Washington, DC, 2018)
In recent years, the world has seen formidable manifestations of citizens’ engagement. By taking to the streets to condemn corruption scandals, by rallying on social media to address growing inequalities, or by participating in global consultations to develop the Sustainable Development Goals (SDGs), ordinary citizens are increasingly eager and able to make their voices heard. At the same time, after several decades of progress, the space for citizens’ voices is shrinking globally as several governments raise legal barriers to constrain actions by civil society organizations (CSOs) and to muzzle the media. In this context, the World Bank Group’s commitment to citizen engagement can catalyze change. This is even more important because achieving the SDGs and the twin goals rests on the active involvement of citizens and local governments.